Efecto de la humedad y de la textura del suelo en el crecimiento y desarrollo del coquito Cyperus rotundus L - Fuentes de Piedrahíta, Cilia L.; Doll, Jerry D. (1976)
Two trials were conducted in the screenhouse of CIAT (Centro Internacional de Agricultura Tropical), located in Palmira, Colombia, to obtain information on how soil characteristics affect the growth of purple nutsedge (Cyperus rotundus L.). One was designed to determine the effect of five levels of soil moisture (saturation and 100, 75, 50 and 25 percent field capacity) on the growth and development of purple nutsedge from four physiographic zones of Colombia (Valle, Córdoba, Magdalena and Tolima). There were no significant differences between the purple nutsedges of the four regions of Colombia, but there was between soil moisture levels. The highest aerial dry matter production, shoot, inflorescence and tuber number was obtained with high soil moisture levels (saturation and 100, and 75 percent field capacity). Equal number of tubers were produced at all three depths. The average number of tubers produced in 120 days was 125 per plant. The second trial was designed to measure the effects of clay, clay loam, sandy and very sandy textured soils on the growth and development of one purple nutsedge ecotype (Valle) under the same five levels of soil moisture as in the first trial. There were significant differences between soil types and moisture levels. Purple nutsedge produced 81 percent more aerial dry matter in heavy textured soils with high moisture levels than in light soils with low soil moisture. Flowering was reduced in both the very sandy and heavy textured soils. No significant differences of tuber number between the three depths was detected, but there was tendency to produce more tubers in the 14 to 21 cm depth with the clay soil. The highest N, P and K percentages in the leaf tissue were found in the light textured soils. The N and K percentages were very similar and much larger than that of P.